Socialization of Utilize Study Depent On Animal Stick Media For Learning To Account in Elementary School Kareng Kidul Probolinggo - Ribut Prastiwi Sriwijayanti; Uswatun Hasanah; Iwing Ade Miranda; Adelia Meira Widirini Prayogi; Wulan Agustin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The Abdimas activity is aimed at Parents in Elementary School Karen Kidul Probolinggo, who is generally affected by the Covid-19 pandemic so the study in their school with online. The existence of this Abdimas activity is to help their parents to learn their children in the house. Abdias activities Based on the collection of information on learning Mathematics 1stClass In Kareng Kidul Elementary School, Probolinggo Regency, Found problems namely : (1) Students still not control count a sum,(2) In the process of learning Teachers still do not use Media that can be Help in clarifying Students understanding of the subject. the conclusion of Animal Stick media addition Can suggest (1) Teachers have to understand Well guide Media products Animal Stick (3) product development further You would better get off update image A contrasting ornament of fine more.